VITAMIN D STATUS AMONG VEGETARIANS AND NON-VEGETARIANS - Baig, Jawed Altaf; Sheikh, Shehnaz A; Islam, Ibnat; Kumar, Mukesh (Journal of Ayub Medical College Abbottabad, 2013)
Background: Vitamin D helps in maintaining bone and muscle health. Vitamin D deficiency is a global problem, with the prevalence of deficiency being widespread in Pakistan. The present study was planned to associate serum vitamin D, Parathyroid Hormone (PTH), calcium and phosphate concentrations with dietary habits of individuals living in urban/rural areas of Sindh, Pakistan. Methods: This was a cross-sectional study at two locations, urban (Karachi) and rural (Haji Goth of Shadadpur city). The study period was May-October 2012 on 176 healthy subjects, aged 20-80 years. Venous blood was collected for analysis of vitamin D, PTH, calcium and phosphorus. Statistical analysis was done using SPSS-18. Statistical differences between variables were determined by student’s t-test and p<0.05 was considered significant. Results: The 176 subjects were divided into non-vegetarians (93, 52.84%) and vegetarians (83, 47.16%) with each group subdivided into urban and rural. The BMI of non-vegetarians vs vegetarians was high (p<0.001). Vitamin D in non-vegetarians vs vegetarians was low (p<0.001). The vegetarians of urban compared to rural had low vitamin D (p<0.05). The PTH of non-vegetarians vs vegetarians was significantly high (p<0.001). Serum calcium was significantly low (p<0.05) in urban and rural subjects on either diet. Conclusion: Non-vegetarians had severe vitamin D deficiency, while vegetarians had vitamin D insufficiency irrespective of belonging to urban or rural area. Keywords: Vitamin D, deficiency, insufficiency, non-vegetarians, vegetarians